1995
DOI: 10.1677/joe.0.1440301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intranasal glucocorticoids on endogenous glucocorticoid peripheral and central function

Abstract: Glucocorticoids are among the most potent antiinflammatory agents that can be used in the treatment of rhinitis. Their mechanisms of action are multiple and complex and a number of reports describe significant systemic effects of locally administered glucocorticoids. In order to evaluate the short-term systemic effects of intranasally administered glucocorticoids, 14 normal healthy subjects were treated with two doses of either budesonide (BUD) or fluticasone propionate (FP) for 2 weeks. Before treatment, at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…In addition, in these studies a short washout time between the experiments was used, 1 -4 weeks. We have previously reported that the hypothalamic -pituitaryadrenal axis is affected for a long time after exposure to low doses of glucocorticoids (29).…”
Section: A Elimam and C Marcusmentioning
confidence: 98%
“…In addition, in these studies a short washout time between the experiments was used, 1 -4 weeks. We have previously reported that the hypothalamic -pituitaryadrenal axis is affected for a long time after exposure to low doses of glucocorticoids (29).…”
Section: A Elimam and C Marcusmentioning
confidence: 98%
“…Table 2 Correlations between serum cortisol concentrations and cortisol receptor characteristics in patients with Cushing's syndrome (n = 13) and in control subjects (n = 14). (7,8). The possible mechanism of this receptor downregulation is poorly understood.…”
Section: European Journal Of Endocrinology (2000) 142mentioning
confidence: 99%
“…It is now well established that the ability of GCs to exert their biological effects requires the presence of a sufficient amount of intact receptor molecules (4,6). There is evidence that GRs undergo down-regulation after exposure to ligand in vitro, in animals and men (7,8). This receptor down-regulation is supposed to be an additional form of negative feedback regulation of GC action, apart from the regulation of GC serum levels by the HPA-axis (6).…”
Section: Introductionmentioning
confidence: 99%
“…This was done to exclude stress as the cause of the difference in cortisol levels the first time the experiment was performed. A long period was left between the measurements because of our previous finding that the hypothalamic-pituitary-adrenal axis is affected for a long time after exposure to low doses of glucocorticoids (28).…”
Section: Subjects and Experimental Protocolmentioning
confidence: 99%